PENGARUH DIMENSI KEADILAN PAJAK DAN TAX MORALE TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK BADAN YANG TERDAFTAR DI KPP PRATAMA KOTA BANDUNG - Dedy Suryadi (Jurnal TEDC, 2016)
This study aimed to examine the effect of taxes and tax fairness dimensions of morale on the level ofcompliance with corporate taxpayers registered in KPP Bandung. Richardson (2006) and Azmi Perumal (2008)explains that there are five dimensions that influence tax compliance behavior, namely: (1) natural justice, (2)reciprocal government, (3) interest, (4) special provisions , (5) tax rate structure. While Mustikasari (2007)that (1) violates ethics, (2) guilt, (3) the principles of living a positive effect on tax compliance behavior.Thestudy was conducted with a questionnaire survey method to test the primary data obtained from 72respondents, using partial least squares analysis (PLS) was used to identify the dimensions of tax fairness andtax morale on tax compliance level agency listed in KPP Bandung. The results showed that the directdimension tax fairness and tax morale significantly affect tax compliance Corporate Taxpayers are registered inKPP Bandung against the Taxpayer compliance rate, in which dimensions of tax justice has a positive effect onthe level of compliance of Corporate Taxpayers and tax nor positive effect on the morale of the Taxpayercompliance rate.Key words: taxes, tax fairness dimensions, tax morale, tax compliance